Impact of tumor‐associated macrophages and BRAFV600E mutation on clinical outcomes in patients with various thyroid cancers. Issue 3 (19th January 2019) - Cho, Jae Won; Kim, Won Woong; Lee, Yu‐mi; Jeon, Min Ji; Kim, Won Gu; Song, Dong Eun; Park, Yangsoon; Chung, Ki‐Wook; Hong, Suck Joon; Sung, Tae‐Yon
Abstract: Background: Tumor‐associated macrophages (TAMs) play a role in thyroid cancer tumor progression and metastasis. This study aimed to investigate the association of TAM density and cluster of differentiation 68 (CD68) expression with thyroid tumors as a prognostic marker and the relationship of these factors with BRAF V600E mutations. Methods: This study included 275 thyroid specimen tissues, including benign and malignant lesions. We compared the clinicopathological features according to thyroid tumor types and evaluated the presence of CD68 expression and BRAF V600E mutations. Results: CD68 positive expression increased with aggressiveness of thyroid tumor histologic grades ( P  < 0.001). In patients with poorly differentiated thyroid cancer (PDTC) and anaplastic thyroid cancer (ATC), CD68 positivity was associated with aggressive adverse clinical outcomes such as extrathyroidal extension, cervical lymph node metastases, and distant metastases ( P  < 0.05). Conclusions: CD68 positivity was more frequent in advanced and aggressive thyroid cancer types such as PDTC/ATC.